A facile spray pyrolysis fabrication of Sm:CdS thin films for high-performance photodetector applications - Shkir, Mohd; Ashraf, I.M.; Khan, Aslam; Khan, Mohd Taukeer; El-Toni, Ahmed Mohamed; AlFaify, S. (Sensors and actuators. A. Physical., 2020)
Development of Sm:CdS thin films based visible light photodetectors for optoelectronic devices. [Display omitted] •Facile fabrication of Sm:CdS thin film photodetector was developed.•High responsivity of 1.01 AW−1 for Sm:CdS compare to pure (0.213 AW−1).•High specific photodetectivity was noted ∼ 2.21 × 1012 Jones for Sm:CdS.•Excellent photosensitivity of ∼ 4.9 × 103 compare to pure CdS (∼ 2.0 × 103).•Very high EQE of ∼257 % was observed for Sm:CdS compare to pure CdS. Achievement of high-performance photodetectors based on CdS is a key field of research and challenge in the current scenario. Here, facile fabrication and characterization of novel samarium (1, 3 and 5 wt.% Sm)-doped CdS thin films for the photodetector applications have been demonstrated. The fabricated films show good crystallinity with crystallites size ranging 18–30 nm. The morphology and homogeneity of Sm-doping ingrown films were confirmed through scanning electron microscopy/energy-dispersive X-ray spectroscopy (SEM/EDX). Field emission SEM study reveals the low dimension nanograins formation and the films are free from voids and cracks. The effects of Sm-doping on linear and nonlinear optical properties of the fabricated thin films have been elucidated. The optical parameters such as refractive index, energy gap, susceptibilities were noticed to be reduced by Sm-doping in CdS thin films. An emission peak around 536 ± 14 nm was observed in PL spectra of pure CdS which was found to be shifted and quenched by Sm-doping. Finally, the photodetector performance of the fabricated thin films has been investigated for 532 nm laser light. The photodetector based on the 1 wt.% Sm:CdS shows an improved performance (higher responsivity of 1.01 AW−1, higher detectivity of 2.21 × 1012 Jones, excellent photosensitivity of ∼4.9 × 103, and very high external quantum efficiency (EQE) of 257 %) compared to pure CdS (responsivity of 0.213 AW−1, detectivity of 7.43 × 1011 Jones, photosensitivity of ∼2.0 × 103, and EQE of 249.70 %). These results propose a much simpler route to achieve high-quality CdS films for photodetector applications.